UPAYA PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (KDRT) MELALUI UNDANG-UNDANG - Nita Yuniarti (Balai Diklat Keagamaan Jakarta, 2020)
The general nature of man is basically inclined towards goodness, but this tendency can change due to three factors. First, when you see an opportunity to do bad things. Second, when there is an unbearable basic need. Third, there is desire that is out of control. So controlling the three factors that cause humans to do bad things must be strived for, so that humans always tend to goodness. Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence, and Law of the Republic of Indonesia Number 17 of 2016 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002, Concerning Child Protection, is one of the state's efforts to block human opportunities to commit crimes in the form of violence in their household. This paper uses a qualitative approach with descriptive methods. The data collection technique is observation through literature study. The problem in this research is the hope of reducing domestic violence behavior after the enactment of the PKDRT Law, but the facts show different things. The results of the study prove that the graph of domestic violence after the enactment of this law is still increasing.